Comparative ecology and ecophysiology of some common pioneer plant species in Sarawak - Layang, Unam (Universiti Malaysia Sarawak (UNIMAS), 2002)
Studies on the ecolong and ecophysiology of some common early successional species were carried out in the nursery of University Malaysia Sarawak, Sarawak, to investigate the effect of soil and nutrients on seddling growth performance. Soil properties were markedly affected by seedling establishment in several ways. Growth performances were significantly limited by soil nutrient availability. Analysis of variance show that the total biomass was significantly affected by the interaction between soil type and nutrient treatments in most of the study species.